A multicenter survey of antimicrobial susceptibility of Prevotella species as determined by Etest methodology. (August 2018) - Ulger Toprak, Nurver; Veloo, Alida C.M.; Urban, Edit; Wybo, Ingrid; Justesen, Ulrik S.; Jean-Pierre, Helene; Morris, Trefor; Akgul, Oncu; Kulekci, Guven; Soyletir, Guner; Nagy, Elisabeth; ,
Abstract: Knowledge about the antimicrobial susceptibility patterns of different Prevotella species is limited. The aim of this study was to determine the current antimicrobial susceptibility of clinical isolates of Prevotella species from different parts of Europe, Kuwait and Turkey. Activity of 12 antimicrobials against 508 Prevotella isolates, representing 19 species, were tested according to Etest methodology. EUCAST, CLSI and FDA guidelines were used for susceptibility interpretations. All Prevotella species were susceptible to piperacillin/tazobactam, imipenem, meropenem, tigecycline and metronidazole. Ampicillin/sulbactam and cefoxitin also showed good activity. Ampicillin, clindamycin, tetracycline and moxifloxacin were less active; 51.2%, 33.7%, 36.8% and 18.3% of isolates were non-susceptible, respectively. A total of 49 (9.6%) isolates were resistant to three or more antimicrobials. Prevotella bivia was the most prevalent species (n = 118) and accounted for most of the multidrug-resistant isolates. In conclusion, the level of non-susceptibility to antimicrobials, which may be used for treatment of infections involving Prevotella species, are a cause of concern. This data emphasizes the need for species level identification of clinical Prevotella isolates and periodic monitoring of their susceptibility to guide empirical treatment. Highlights: Twelve antimicrobials were tested on 508 Prevotella clinical isolates from 13 countries. All isolates were susceptible to piperacillin/tazobactam, carbapenems, tigecycline and metronidazole. High non-susceptibility rate was found to ampicillin, clindamycin, tetracycline and moxifloxacin. A total of 49 (9.6%) Prevotella isolates were resistant to three or more antimicrobials. P. bivia was most prevalent (n = 118), accounting for most resistant isolates.